DEVELOPMENT OF WRITTEN SPEECH COMPETENCE OF PRIMARY CLASS STUDENTS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The concept of developing written speech in the classes of native language and reading literacy, forms and means of developing written speech in native language classes, the use of interactive methods in improving written literacy, their importance, teaching methods, methods and tools illuminated. Examples of practical application of scientific and theoretical information are also presented. In the process of education, it is said about the communicative skills that must be formed in students by achieving speech development. and the scientific views of linguists and Methodist scientists on increasing written literacy, independent expression of one's opinion, acquisition of speech culture are analyzed.